Sifting through the Controversy: The Moral Problem in Roald Dahl’s Matilda (Journal of the College of Education for Women, 2026)
Since 1988, Roald Dahl's Matilda has garnered praise and criticism. This descriptive and analytical study addresses Matilda's moral dilemma with her parents and the authoritarian school headmistress. The paper examines whether the novel promotes moral empowerment through teaching or moral transgression by legitimizing a child's punishment of an adult authority figure. Child ethics, authority, and education's function in moral development inform the study's moral and educational criticism framework. The article examines Matilda's situation as a brilliant youngster living in a difficult family and subjected to school mistreatment through close textual analysis. The ethical ramifications of her acts against power-hungry adults are highlighted. Critical responses to the novel fell into two factions, according to the study. Matilda supporters see education, reading, and intellectual progress as self-defense and moral agency. The story encourages parents and educators to transform the family and school as social institutions. The tale may encourage disobedience, dishonesty, and indirect aggression by depicting adult authority as wrong and deserving of punishment, according to opponents. The study indicates that Matilda exposes the moral repercussions of ignored responsibility and oppressive authority, not just disobedience against family and school. The narrative portrays education as moral empowerment rather than corruption. Dahl highlights the power disparity between children and adults, inviting readers to reconsider parents' and educators' moral responsibility while framing Matilda's actions as a response to injustice rather than a rejection of moral order.